Human dynamics with limited complexity. Issue 4 (4th July 2019) - Levene, Mark; Fenner, Trevor; Loizou, George
ABSTRACT: Human dynamics suggest statistical models that may explain and provide us with better insight into human behaviour in various social contexts. Here, we provide a critical overview of human dynamics in the context of complex systems and sociophysics. One of the principal ideas in sociophysics is that, in a similar framework to that of statistical physics, individual humans can be thought of as 'social atoms', each exhibiting simple individual behaviour and possessing limited intelligence, but nevertheless collectively giving rise to complex social patterns. In this context, we propose a generative multiplicative decrease process having an attrition function that controls the rate of decrease of the population at each stage of the process. The discrete solution to the model takes the form of a product, and a continuous approximation of this solution is derived via the renewal equation that describes age-structured population dynamics. We also investigate some limited complexity variations of the attrition function within this model.